2021
DOI: 10.5937/esd2102029m
|View full text |Cite
|
Sign up to set email alerts
|

Trends and strategic approach to establishing work/life balance of managers and other employees

Abstract: The purpose of the paper is presenting the most noticeable trends in establishing work/life balance of managers and other employees worldwide. Due to global changes, establishing work/life balance of employees is considered a strategic topic for human resource management (HRM). The research was conducted through a thorough analysis of various theoretical and empirical studies from the previous period, both domestically and abroad, with the aim of determining the extent to which companies have integrated employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Managers can implement various work/life balance practices and benefits, both privately and organized by their companies. Thereby, from the offered practices and benefits by the company, each individual manager should choose the ones that are most significant to them, depending on their current career position, living conditions, life circumstances, as well as personal values, needs, goals and priorities (Mladenović & Krstić, 2021c).…”
Section: Discussion Of the Effects Of Manager's Work/life Balancementioning
confidence: 99%
“…Managers can implement various work/life balance practices and benefits, both privately and organized by their companies. Thereby, from the offered practices and benefits by the company, each individual manager should choose the ones that are most significant to them, depending on their current career position, living conditions, life circumstances, as well as personal values, needs, goals and priorities (Mladenović & Krstić, 2021c).…”
Section: Discussion Of the Effects Of Manager's Work/life Balancementioning
confidence: 99%
“…Approximately 80 percent of disabled individuals live in developing countries (Eide, Muderedzi, Braathen, & Stray-Pedersen, 2017). As work/life balance is influenced by a variety of factors that are unique to each management and employee and can vary over time (Mladenović & Krstić, 2021).…”
Section: I S H L I N N W E I S E R K R I S Z T I N a D A J N O K Imentioning
confidence: 99%
“…Due to changes in recent socio-demographic trends, such as a larger number of women entering the work field, more challenging work demands, faster lifestyles and increased need for elderly care (Mladenović & Krstić, 2021b), it can be concluded that work and private life should not be viewed as two segregated parts of an employee's life, but rather as parts of life which both require as much time, energy and devotion (Hein, 2005). Since work and private life have become equally important for employees of both genders (Vandello et al, 2013), an interconnection or overlap of these two life spheres can be noticed, as presented in Figure 1, with events in each sphere affecting the other one (Lingard & Francis, 2005).…”
Section: Introductionmentioning
confidence: 99%